2021 IEEE/ACM 43rd International Conference on Software Engineering (ICSE) 2021
DOI: 10.1109/icse43902.2021.00092
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Matching Bug Reports With Related App Reviews

Abstract: App stores allow users to give valuable feedback on apps, and developers to find this feedback and use it for the software evolution. However, finding user feedback that matches existing bug reports in issue trackers is challenging as users and developers often use a different language. In this work, we introduce DeepMatcher, an automatic approach using stateof-the-art deep learning methods to match problem reports in app reviews to bug reports in issue trackers. We evaluated DeepMatcher with four open-source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The general purpose LMs were 'bert-baseuncased', 'roberta-base', 'xlnet-base-cased' and 'distilbertbase-uncased', while the classical IR models were VSM, LDA and LSI. In addition, we also evaluated TraceNN [22] as discussed in Section 8, and DeepMatcher [64].…”
Section: Rq1: How Well Does Nltrace Perform Without the Benefit Of Do...mentioning
confidence: 99%
See 1 more Smart Citation
“…The general purpose LMs were 'bert-baseuncased', 'roberta-base', 'xlnet-base-cased' and 'distilbertbase-uncased', while the classical IR models were VSM, LDA and LSI. In addition, we also evaluated TraceNN [22] as discussed in Section 8, and DeepMatcher [64].…”
Section: Rq1: How Well Does Nltrace Perform Without the Benefit Of Do...mentioning
confidence: 99%
“…Our study further investigates the effectiveness of applying LM-based approaches to address the text-to-text tracing task instead of text-tocode. Other LM based trace models, such as DeepMatcher [64], used DistillBert as an alternative encoder of VSM and RNN; however the output of DistillBert was directly applied to Cosine Similarity without fine-tuning. We argue that this method is relatively weak because it only uses the knowledge from the pretraining stage without the benefit of calibration with the target project through fine-tuning.…”
Section: Related Workmentioning
confidence: 99%
“…Wu et al [41] created a Chinese dataset from the Chinese Apple App Store and built a regression model to identify key features of app by analyzing app description and positive/negative user reviews. Haering et al [50] focused on the gap between technically-written bug reports with colloquially-written app reviews, extracting issues from app reviews and matching them to bug reports. Henao et al [51] proposed a framework for mining feature requests and bug reports from tweets and app store reviews via transfer learning.…”
Section: B App Review Miningmentioning
confidence: 99%
“…Other researchers tried to match user reviews with bug reports written by developers. For example, Häring et al [6] proposed an automatic approach DeepMatcher to match problem reports in app reviews to bug reports in issue trackers by using deep learning algorithms. Palomba et al proposed CRISTAL [7] to trace informative crowd reviews into code changes, in order to monitor the extent to which developers accommodate crowd requests and follow-up user reactions as reflected in their ratings.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Although informative user reviews were reported to have valuable information (e.g., feature requests and bug reports) for developers, there is still no clarity on whether user reviews are actually taken into account by developers and implemented in the new release. Some researchers traced informative user reviews to source code changes to support evolution of successful apps [6] [7]. However, these authors focused their exploration on open source apps, rather than all the mobile apps.…”
Section: Introductionmentioning
confidence: 99%